Evaluation of the Carbon Footprint, Water Footprint,Nutrient Profiles and Cost of Sustainable Menus PlannedWith Digital Modeling - Beyhan, Y; Adiyan, NN; Dayi, T (Food Science & Nutrition)
This study aimed to evaluate the sustainability of digital program menus (DPMs) and compare them with the Turkish National Menu Planning Guide (TNMPG) and internet-accessible menus (IAM). A menu planning program was developed in Microsoft Excel, which also calculates the sustainability criteria (carbon footprint, water footprint, NRF 9.3, SAIN-LIM and cost) of the menus with the recommendations of the TNMPG. The digital menus were compared with the sustainability criteria of the TNMPG sample menus and menus accessed from the internet. DPM was found to be similar to the sample menus of the TNMPG in terms of sustainability features. All the meals on the menus were similar in terms of their carbon footprint (p > 0.05), whereas the II-type meals of the kindergarten menu of DPM and the IV-type meals of the hospital menu of IAM were found to have greater water footprints (p < 0.05). Some meals (II/III) in DPM had higher NRF-9.3 scores (p < 0.05). The I-type meals of the kindergarten and prison menus of DPM and the II-type meals of the prison menu were found to have significantly higher costs (p < 0.05). Digitalization could provide great benefits in service, as digital menus in food services can be prepared in a very short time, and sustainability criteria can be easily achieved.
Keywords: cost; digital modeling; ecological impac